IDENTIFIKASI JAMUR DAN BAKTERI PADA BEBERAPA PENGGUNAAN LAHAN DI KOTA SAMARINDA - Zainudin Zainudin; Roro Kesumaningwati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
Land use change indirectly affects soil biological fertility. Changes in forest land use into land use have an impact on the impact of soil organic matter which will affect the microorganism population. Microorganisms and carbon in general are more sensitive to changes in land use. Microorganism biomass changes more rapidly after land use changes. The research objective was to detect soil fungi and bacteria on different land uses, namely mixed forest, seasonal crop farming, and former coal mining land. This research will be conducted for 1 (one) fiscal year. This research includes the following stages: soil survey for sampling, and bacterial and fungal surveys conducted in the laboratory. The research method for observing soil properties is random sampling of soil at each land use, namely seasonal crop land, mixed garden land, secondary forest, and former coal mining land. Random sampling of soil by means of a composite. Composite soil samples were taken from 5 sub-samples at a depth of 0-30 cm and 30-60 cm, in order to obtain one composite sample for each different land use and soil depth. The results showed that the fungi found were Mucor and Trichoderma with the highest total fungal population of 3.2 x 104 Cfu / gr found in seasonal crop fields with a depth of 30-60 cm. The bacteria found were from the Genus Azotobacteraceae with the highest total population of 1.5 x 105 Cfu / gr found in seasonal plantations and secondary forest with a depth of 30-60 cm.